Brain Research The Necessity for Separating Sites, Actions and Functions - Meeker, Mary.; SOI Systems, Vida, OR. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
Educators, as applied scientists, must work in partnership with investigative scientists who are researching brain functions in order to reach a better understanding of gifted students and students who are intelligent but do not learn. Improper understanding of brain functions can cause gross errors in educational placement. Until recently, the popularity of IQ scores has curtailed the understanding of the measurement of demonstrated functions in human intelligence. Tests based on the Structure of Intellect (SOI), first published in 1975, evaluate 26 abilities that are highly predictable of success in school. They are based on the theories of J. P. Guilford who differentiated 96 kinds of intelligence that could be identified factorially. The Guilford model predicted the separation of sites of brain functions clearly. The Contents dimension of the model, comprised of Figural Intelligence, Symbolic Intelligence, and Semantic-Verbal Intelligence, actually maps the functions of the right, cross-over, and left hemisphere sites. IQ scores are now used as criteria for identifying giftedness in only a few states. Giftedness is recognized as a multi-dimensional human phenomenon and with more concern for the kinds of giftedness shown by an individual as can be measured by the SOI tests. (VW)
ERIC Note: Excerpts from a paper presented at the "Neurobiology Conference of Extraordinary Giftedness" (New York, NY, April 1985).
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Ability Identification; Brain; Cognitive Tests; Educational Research; Elementary Secondary Education; Gifted; Intelligence Differences; Intelligence Quotient; Neurological Organization; Talent Identification; Theory Practice Relationship; Structure of Intellect; Guilford (J P); Reports, General; Speeches/Meeting Papers